Determinan Struktur Modal dan Nilai Perusahaan - Mukmin Pohan; Maya Sari; Adi Munasib; Radiman Radiman (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2020)
The purpose of this study is to formulate a determinant model of capital structure and firm value. The population of this study is the tourism industry sector companies listed on the Indonesia Stock Exchange for the period 2013-2018. In this study the entire population is sampled (Total Sampling). Data collection procedures by collecting audited (annual report) financial report data issued by the Indonesia Capital Market Directory (ICMD). The data analysis technique used is path analysis. The results showed that partially profitability, institutional ownership and firm size had a significant effect on capital structure while company growth had no significant effect on capital structure. Simultaneously the profitability variables, institutional ownership, company growth and company size affect the capital structure. Partially profitability, institutional ownership, company size and capital structure have a significant effect on firm value, while company growth does not significantly influence firm value Simultaneously profitability, Institutional ownership, company size, company growth and capital structure have a significant effect on company value in the sector tourism industry.